Electroweak symmetry breaking in Sp(6) gauge-Higgs unification model - Nobuhito Maru; Akio Nago (Nuclear Physics B)
We study the electroweak symmetry breaking in a five dimensional Sp(6) gauge-Higgs unification model where the weak mixing angle is predicted to be sin2⁡θW=1/4 at the compactification scale. We find that the correct pattern of electroweak symmetry breaking is realized by introducing a 4-rank totally symmetric representation additionally. Furthermore, one-loop renormalization group equation analysis show that the weak mixing angle at the weak scale can be in good agreement with the experimental data by introducing some fermions in the adjoint representation.